1996
DOI: 10.1002/mds.870110503
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of severe postural cerebellar tremor in multiple sclerosis by chronic thalamic stimulation

Abstract: Tremor can be particularly disabling in patients with multiple sclerosis (MS) and is mildly improved by drug treatment. The efficiency of stereotactic thalamotomy has been reported in a small number of patients but was counterbalanced by severe postoperative complications. Stimulation of the thalamic ventral intermediate nucleus, which is a less aggressive surgical method, is efficient in essential and in parkinsonian tremors. We report here the results of thalamic stimulation in 13 patients with MS with tremo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 21 publications
4
54
1
3
Order By: Relevance
“…5 Several studies have examined the effects of thalamic DBS on MS tremor (Table 2). [33][34][35][36][37][38] The majority of these were single-center studies with small sample sizes. One study reported unilateral DBS of the Vim in 13 MS patients (11 relapsing progressive; 2 relapsing remitting) after a follow-up of up to 26 months.…”
Section: Multiple Sclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…5 Several studies have examined the effects of thalamic DBS on MS tremor (Table 2). [33][34][35][36][37][38] The majority of these were single-center studies with small sample sizes. One study reported unilateral DBS of the Vim in 13 MS patients (11 relapsing progressive; 2 relapsing remitting) after a follow-up of up to 26 months.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…One study reported unilateral DBS of the Vim in 13 MS patients (11 relapsing progressive; 2 relapsing remitting) after a follow-up of up to 26 months. 33 All patients were diagnosed with severe cerebellar tremor due to MS. There was a decrease in tremor amplitude in all patients and long-term reduction of tremor in 69%.…”
Section: Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…14, Of the 38 articles identified for DBS of the thalamus, 16 articles met criteria. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] The review of DBS of the globus pallidus consisted of all 10 articles identified, [56][57][58][59][60][61][62][63][64][65] and DBS of the subthalamic nucleus was based on all 6 articles identified. 62,[66][67][68][69][70] There were 52 articles for adrenal medullary transplantation, but the review includes only the 9 that met criteria.…”
mentioning
confidence: 99%
“…Geny and colleagues observed that the effective VIM site in multiple sclerosis is often dorsal and lateral to the VIM site that is effective in Parkinson's disease, and that the exact location of the stimulator within the VIM must be selected with attention to the somatotopic distribution within the nucleus. 11 Nguyen and Degos found that stimulation of the upper VIM region was most effective in controlling proximal tremor, while stimulation of the lower part of the VIM was most effective in controlling distal tremor. 8 In most cases, stimulator implantation was unilateral, but bilateral implantations (either staged or simultaneous) and implantations contralateral to a previous thalamotomy were also reported.…”
Section: Surgical Proceduresmentioning
confidence: 99%